2021
DOI: 10.5194/jbji-6-329-2021
|View full text |Cite
|
Sign up to set email alerts
|

Timing of debridement, antibiotics, and implant retention (DAIR) for early post-surgical hip and knee prosthetic joint infection (PJI) does not affect 1-year re-revision rates: data from the Dutch Arthroplasty Register

Abstract: Abstract. Debridement, antibiotics, and implant retention (DAIR) is a procedure to treat a periprosthetic joint infection (PJI) after total hip arthroplasty (THA) or total knee arthroplasty (TKA). The timing between the primary procedure and the DAIR is likely a determinant for its successful outcome. However, the optimal timing of a DAIR and the chance of success still remain unclear. We aimed to assess the risk of re-revision within 1 year after a DAIR procedure and to evaluate the timing of the DAIR in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
9
1
2
Order By: Relevance
“…All 16 patients in our cohort underwent surgical intervention for the 18 PJIs. For the treatment of acute PJI with DAIR, the literature reports success rates of 83%-90% [19][20][21]. However, in our cohort, 2/14 (14.28%) patients undergoing DAIR had treatment success, and only 5/18 (27.77%) of all of the joints had successful PJI management.…”
Section: Discussioncontrasting
confidence: 54%
“…All 16 patients in our cohort underwent surgical intervention for the 18 PJIs. For the treatment of acute PJI with DAIR, the literature reports success rates of 83%-90% [19][20][21]. However, in our cohort, 2/14 (14.28%) patients undergoing DAIR had treatment success, and only 5/18 (27.77%) of all of the joints had successful PJI management.…”
Section: Discussioncontrasting
confidence: 54%
“…19,20 No consensus has been reached over cemented versus uncemented implants, with some sources citing cemented implants as having a greater failure risk. 19,34 Hip arthroplasty shows higher success rates for DAIR over knee arthroplasty, 1,20 but shoulder arthroplasty shows a DAIR success rate of 75%, in keeping with hip and knee cohorts. 20…”
Section: Implant Factorsmentioning
confidence: 85%
“…Nevertheless, DAIR remains a favourable option in patients with an average duration of symptoms of less than three weeks. 7,16,19,31 The time from index surgery or implant age is a heavily debated topic, with some literature suggesting that DAIR should only be performed if the duration from the index surgery is less than one month, 7 whereas others have suggested that this time frame could be extended to three months 3,8,16,19,34 or even a year. 18 It has been suggested that when the implant is well fixed and the PJI is caused by a less virulent organism in an otherwise viable joint, the implant age is not significant.…”
Section: Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Some current studies demonstrate the DAIR performance within three months of surgery has acceptable success rates. For instance, De Vries et al 12 achieved an 84% rate of component retention. However, these authors mentioned the fundamental role of a stable component, an identified and treatable organism, symptoms for less than three weeks, and intact soft parts.…”
Section: New Conceptsmentioning
confidence: 99%